Dissimilar trend of nonlinearity in ultrasound transducers and systems at resonance and non-resonance frequencies - Ghasemi, N.; Zare, F.; Davari, P.; Vilathgamuwa, M.; Ghosh, Arindam; Langton, C.; Weber, P. (2017)
Several factors can affect performance of an ultrasound system such as quality of excitation signal and ultrasound transducer behaviour. Nonlinearity of piezoelectric ultrasound transducers is a key determinant in designing a proper driving power supply. Although, the nonlinearity of piezoelectric transducer impedance has been discussed in different literatures, the trend of the nonlinearity at different frequencies with respect to excitation voltage variations has not been clearly investigated in practice. In this paper, to demonstrate how the nonlinearity behaves, a sandwich piezoceramic transducer was excited at different frequencies. Different excitation signals were generated using a linear power amplifier and a multilevel converter within a range of 30–200 V. Empirical relation was developed to express the resistance of the piezoelectric transducer as a nonlinear function of both excitation voltage and resonance frequency. The impedance measurements revealed that at higher voltage ranges, the piezoelectric transducer can be easily saturated. Also, it was shown that for the developed ultrasound system composed of two transducers (one transmitter and one receiver), the output voltage measured across receiver is a function of a voltage across the resistor in the RLC branches and is related to the resonance frequencies of the ultrasound transducer.